Optical properties and thermionic emission in solar cells with InAs quantum dots embedded within GaNAs and GaInNAs. (November 2015) - Polojärvi, Ville; Pavelescu, Emil-Mihai; Schramm, Andreas; Tukiainen, Antti; Aho, Arto; Puustinen, Janne; Guina, Mircea
Graphical abstract: Abstract: The optical properties of p-i-n solar cells comprised of InAs quantum dots embedded within GaNAs and GaInNAs quantum wells are reported. Strain compensating and mediating GaNAs and GaInNAs layers shift the photoluminescence emission as well as absorption edge of the quantum dots to longer wavelengths. GaNAs and GaInNAs quantum wells contribute also to extending the absorption edge. In addition, the use of GaNAs and GaInNAs layers enhances the thermal escape of electrons from QDs by introducing steps for electrons to the GaAs conduction band.